Biopolymer Nanocomposites for Sustainable UV Protective Packaging - Gore, Anil H.; Prajapat, Amrutlal L. (Frontiers in Materials, 2022)
The development of green, eco-friendly and sustainable packaging materials is a major challenge in the field of nanoscience and nanotechnology. Advancements in the designing biopolymeric nanocomposites for packaging applications have been established by considering features like biodegradability, environmental friendliness, mechanical properties, cost, safety, etc. Other properties such as thickness, weight, transparency, practicability, recyclability, antimicrobial, porosity, leaching effect, light protective capability, etc. need to be considered during the fabrication of next-generation packing materials for multifaceted applications. Of these, the ultraviolet (UV) protective properties of the designed nanocomposites for sustainable packaging applications are extremely important. The UV protective properties of the packaging materials can be modulated by adding a minute amount of biocompatible nanomaterials with maximum absorption properties in the UV region (200–400 nm). UV light absorption is very important to avoid loss or changes in intrinsic chemical, physical, and biological properties/content of foods, pharmaceuticals, beverages, and so forth during storage and transportation. In the current review, we highlight the principle of UV light protection, the selection of nanomaterials, and the design of nanocomposite films, including the properties and applications of biopolymeric nanocomposite materials for UV protective sustainable packaging. Lastly, the current challenges and prospects of sustainable UV protective packaging are also discussed to provide insights into the future of next-generation packaging technologies.